The Effect of Smoking Habit on Vitamin D Status in Adults in Indonesia - Lorensia, Amelia; Suryadinata, Rivan Virlando (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Smoking will reduce the metabolism of vitamin d in the body. Indonesia, as a tropical country that has a high level of sun exposure, is one with a high prevalence of smokers. Early identification of vitamin D status can be used as a preventive measure for risks associated with vitamin D deficiency. This study aimed to determine the smoking behaviour with vitamin D status. This research was conducted in April -November 2021. The research design was cross-sectional, using purposive sampling method. Variable was smoker behaviour, vitamin D status, and vitamin D deficiency. The differences between vitamin D status and smoker behaviour in smoker and non-smoker group used chi-square test and the relationship used contingency coefficient. This study involved 144 subjects, consisting of 73 non-smokers and 71 smokers. The groups at risk for vitamin D deficiency were 17 non-smokers (23.29%) and 31 smokers (43.66%). The smokers group had 2,553 times higher risk of vitamin d deficiency than non-smokers. There was a significant difference between smokers and non-smokers on 25(OH)D level vitamin D status. And there was a significant relationship between vitamin D status in smokers and non-smokers. There was a weak relationship between smokers and non-smokers on vitamin D status.